2011
DOI: 10.1007/s12192-011-0271-9
|View full text |Cite|
|
Sign up to set email alerts
|

Increased heat shock protein 70 levels in induced sputum and plasma correlate with severity of asthma patients

Abstract: Damage-associated molecular pattern molecules such as high-mobility group box 1 protein (HMGB1) and heat shock protein 70 (HSP70) have been implicated in the pathogenesis of asthma. The aim of our study was to examine the induced sputum and plasma concentrations of HSP70 in asthmatic patients to determine their relationship with airway obstruction. Thirty-four healthy controls and 56 patients with persistent bronchial asthma matched for gender and age were enrolled in this study. Spirometry measurements were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…pegreffii was increased in L4s compared with L3s, which may be linked to a response of the parasite to the heat stress that immediately follows infection [ 32 ]. HSPs 70 from mites, black flies, midges and cockroaches are known allergens and mediators of allergic contact hypersensitivity [ 33 , 34 ]; in addition, levels of HSPs 70 are increased in the sputum and plasma of asthmatic patients compared with healthy controls [ 35 ], while antibodies against these proteins are associated with a number of immunological disorders, such as allergy to metals [ 36 ]. Based on this knowledge, it is therefore plausible that antibodies against Anisakis HSPs 70, whose expression is increased upon host infection [ 32 ], may play a key role in allergic responses to these parasites.…”
Section: Discussionmentioning
confidence: 99%
“…pegreffii was increased in L4s compared with L3s, which may be linked to a response of the parasite to the heat stress that immediately follows infection [ 32 ]. HSPs 70 from mites, black flies, midges and cockroaches are known allergens and mediators of allergic contact hypersensitivity [ 33 , 34 ]; in addition, levels of HSPs 70 are increased in the sputum and plasma of asthmatic patients compared with healthy controls [ 35 ], while antibodies against these proteins are associated with a number of immunological disorders, such as allergy to metals [ 36 ]. Based on this knowledge, it is therefore plausible that antibodies against Anisakis HSPs 70, whose expression is increased upon host infection [ 32 ], may play a key role in allergic responses to these parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an estimated 3.9 million South Africans were affected by asthma in 2012, accounting for 1.5% of deaths in this country every year [ 95 ]. Taking into account the cytoprotective roles of HSPs in response to cellular insults, several authors have reported the over-expression of Hsp70 in asthmatic patients [ 96 , 97 ]. Surprisingly, recent studies have suggested that intracellular synthesis of Hsp70 chaperones in airways and alveolar sacs of asthma patients correlate with the deleterious effects and severity of the disease, probably by forming part of the inflammatory complex, where it may up-regulate THP-1 synthesis by inducing CD23 expression in the Th2 environment [ 98 , 99 , 100 ].…”
Section: Hsps In Human Inflammatory Diseases (Hids) and Cancermentioning
confidence: 99%
“…The activity of HSPA1 in the airway epithelium was linked to mucin secretion [ 32 , 33 ] and protection against genotoxic agents [ 34 ]. In turn, extracellularly-released HSPA1, as a damage-associated molecular pattern (DAMP) molecule, has been attributed to the inflammatory responses of the airway epithelium [ 35 , 36 , 37 ] and the pathogenesis of severe respiratory diseases [ 35 , 38 ]. However, the question of why HBEC, as well as other somatic cells, need HSPA2, HSPA1, and other cytoplasmic/nuclear HSPA paralogs remains unanswered.…”
Section: Discussionmentioning
confidence: 99%